2014
DOI: 10.2304/csee.2014.13.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Civic Education in Hong Kong: Why is it Not an Independent Subject?

Abstract: Internationally there have been serious efforts to identify effective modes of delivering civic education for preparing youth for the future challenges of citizenship. This article addresses the research question, 'why is an independent subject not preferred in civic education by Hong Kong civic education teachers?'. It starts with a brief review of international debates and of the development of civic education policy in Hong Kong. Then it moves on to discuss why teachers tend to reject civic education as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Another important observation was that Hong Kong Chinese students were able to construct their own concepts and understanding through experiential learning, in particular after engaging them in enquiry activities for conceptual development. This kind of development can be described as political socialisation, which is an important outcome by schools which have long been considered as influential political socializing agents (Leung and Ng, 2014). For citizenship education, Leung (2006) found that issues-based teaching, experiential learning and teachers with credibility were significant political socialising factors for active democratic citizenship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important observation was that Hong Kong Chinese students were able to construct their own concepts and understanding through experiential learning, in particular after engaging them in enquiry activities for conceptual development. This kind of development can be described as political socialisation, which is an important outcome by schools which have long been considered as influential political socializing agents (Leung and Ng, 2014). For citizenship education, Leung (2006) found that issues-based teaching, experiential learning and teachers with credibility were significant political socialising factors for active democratic citizenship.…”
Section: Discussionmentioning
confidence: 99%
“…Nationalistic education refers to “educational programmes aiming at cultivating people’s knowledge about the nation state and instilling a sense of national identity to the nation state” (Leung, 2003a, p. 9). Meanwhile, civic education in Hong Kong is also regarded as inadequate for preparing youths for democratic citizenship (Leung, 2006), and that it is usually misunderstood by teachers as extra-curricular activities with little content knowledge (Leung and Ng, 2014). Recently, a study also found that some teachers in Hong Kong might not be able to differentiate among moral education, civic education and National Education (Wong et al , 2016).…”
Section: Citizenship Education Active Citizenship and Ngosmentioning
confidence: 99%
“…Hong Kong has adopted an executive-led approach for public governance both before and after the 1997 transition of sovereignty (Cheung, 2007). In contemporary Hong Kong, government officials have been seeking to reinforce the identity of Hong Kong people as subjects within a depoliticized city, focusing on financial and business activities on Chinese soil (for details, see Leung & Ng, 2014). To that end, civic education has largely de-emphasized politics.…”
Section: Comparing Societal Contexts and Educational Policies In Hong Kong And Singaporementioning
confidence: 99%
“…Hong Kong has a long tradition of student activism, but only on a few occasions did secondary school students play an active role in social movements before the 2010s. This is largely because of the city's de-politicized education system, which was shaped partly by an authoritarian colonial government (Leung and Ng 2014) and partly by its Chinese education culture that promotes examination-oriented teaching (Tsao et al 2018;Wong 2016). A fresh wave of student movement only emerged with the establishment of Scholarism by the 15-year-old Joshua Wong in 2011, which culminated in the Anti-National Education Movement in 2012 (Kan 2012).…”
Section: Student Activism In Hong Kong: Breaking the Norm Of "De-politicization"mentioning
confidence: 99%